Investigation Of The Status Of The Natuna Marine Zone And Indonesian Oceanic Defense Technique Within The South China Ocean Debate - Haryani, Tinok -; Setiyono, Joko - (Faculty of Law, Universitas Pekalongan, 2024)
A country's borders and area have a huge affect on its sway. Proprietorship debate are a common source of regional clashes, especially in oceanic locales. Particularly, China's claims to the South China Ocean and Indonesia's sea sway within the Natuna Ocean cover. The reason of this investigate is to donate a more exhaustive understanding of the state of undertakings within the Natuna Ocean locale as well as Indonesia's eagerly for sea defense in connection to the South China Ocean struggle. Utilizing regulating lawful audit procedures, this examination was made. This ponder highlights Indonesia's oceanic sway based on related national laws and the 1982 UN Tradition on the Law of the Ocean (UNCLOS). In any case, China claims sway over the locale utilizing the Nine Dabbed Line Outline. In order to protect its sway and marine security within the Natuna Ocean, Indonesia must act rapidly to address this matter by reinforcing its equipped powers and discharging a challenge note. In this way, settling this oceanic debate and supporting Indonesia's position in ensuring its sway depend on an mindfulness of and adherence to worldwide law.